Employment Strategies and Equal Opportunities for Men and Women - Vladimirova, Katia (Research Papers, 2008)
In the last decade the emphasis of the strategic and political documents of the European Union is placed on the necessity to achieve equal rights for men and women in all spheres of public life, and especially, in the sphere of labour, as one of the prerequisites for social equality in other spheres.The present study aims at evaluating the influence of the strategy and policy of employment in Bulgaria on equal rights for women in the employment sphere.The survey is made from the viewpoint of the modern concept of gender equilibrium, the European and the Bulgarian strategy on employment and the current annual national employment action plans. While the study focuses on Bulgaria, the EU approaches and criteria are used, which are designed to evaluate the progress of all member countries in implementing common policies and strategies, including those involving equal opportunities for men and women on the labour market.To study the influence of the strategy, policies and plans aimed at increasing employment, and more specifically, equal job rights for men and women, the paper attempts to analyze the achievements in the sphere of equal rights for men and women. The paper outlines the key tendencies, problems and challenges for the Strategy, including the incorporated policies for Bulgaria, on the one hand, and makes a survey of the impact of the past policies in the sphere of employment and equal rights on the labour market, on the other hand. The findings of the study are the basis for the proposals and recommendations for future development of an active employment policy intended to promote, to a greater degree, a real, actual equilibrium between the professional and the family life for both sexes individually and jointly. An overview of the basic challenges and openings studied up to now has been made. At the same time the paper points out new challenges and emerging openings.